The agency of patients and carers in medical care and self-care technologies for interacting with doctors - Nunes, Francisco; Andersen, Tariq; Fitzpatrick, Geraldine (Health informatics journal, 2019)
People living with Parkinson's disease engage in self-care for most of the time but, two or three times a year, they meet with doctors to re-evaluate the condition and adjust treatment. Patients and (informal) carers participate actively in these encounters, but their engagement might change as new patient-centred technologies are integrated into healthcare infrastructures. Drawing on a qualitative study that used observations and interviews to investigate consultations, and digital ethnography to understand interactions in an online community, we describe how patients and carers living with Parkinson's participate in the diagnosis and treatment decisions, engage in discussions to learn about certain topics, and address inappropriate medication. We contrast their engagement with a review of self-care technologies that support interactions with doctors, to investigate how these artefacts may influence the agency of patients and carers. Finally, we discuss design ideas for improving the participation of patients and carers in technology-mediated scenarios.